AGE-RELATED MACULAR DEGENERATION, PHATOPHYSIOLOGY, CURRENT TREATMENT AND THERAPEUTIC PERSPECTIVES - Patrycja Jędrzejewska-Rzezak; Adam Żuczek; Kinga Dyndal; Marcelina Broda; Olga Żuczek; Katarzyna Urbańska; Izabela Szczap; Anna Hawryluk; Kamil Marzec; Aleksandra Mokrzycka; Wojciech Kupczak; Kinga Bujak (International Journal of Innovative Technologies in Social Science, 2025)
Age-related macular degeneration (AMD) is a disease leading to severe central vision loss and blindness in people over 60 years. [1] The pathogenesis of this disease is multifactorial and complex interactions of metabolic, functional genetic, and environmental factors - it is not fully known. [2] For the above reasons, the effectiveness of the therapies used is limited. Although the disease involves changes in the anatomical and functional complex, including photoreceptors, retinal pigment epithelium (RPE), Bruch’s membrane, and choriocapillaris layer, the essence of the disorder and its earliest stage is the progressive degeneration and atrophv of the RPE cells. leadina conseauentiv to irreversible damaae to photoreceptors. Four processes occurring within the mentioned complex contribute to the development of AMD: lipofuscinogenesis, drusogenesis, inflammation, and neovascularization. [3]